Application of open string ?eld theory to the in?ationary scenario - Franzmann, Guilherme [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This thesis consists in a review of the String Field Theory framework, focusing in the classical properties of the open sector and its possible applications for in?ation. Therefore, we intend to follow the Witten’s prescription and build an action for the Open Bosonic String Field Theory. Then, recognizing that the theory has a tachyonic mode and motivated by the in?ationary scenario, we calculate and consider the tachyonic potential in some order of approximation. As an application, we consider the tachyon ?eld as a possible candidate for the in?aton. In order to work with this proposal, we ?rst review the in?ationary theory and study its modern approach, considering only its classical implications using the slow-roll approximation. Finally, we analyze the tachyonic potential as being the in?aton potential and explore its consequences. As a support, there are four appendices containing some aspects of String Theory, General Relativity, Cosmology and some relevant calculations that were omitted throughout the thesis

Esta tese consiste em uma revisão da estrutura da Teoria de Campo na Corda, focando nas propriedades clássicas do setor da corda aberta e suas possíveis aplicações para in?ação. Portanto, seguiremos a prescrição do Witten e construiremos uma ação para a Teoria de Campo na Corda Aberta Bosônica. Então, percebendo que a teoria tem uma modo taquiônico e motivado pelo cenário de in?ação, calcularemos e consideraremos o potencial taquiônico em alguma ordem de aproximação. Como aplicação, tomaremos o campo taquiônico como um candidato possível para o in?aton. A ?m de trabalhar com esta proposta, revisaremos primeiramente a teoria in?acionária e estudaremos sua abordagem moderna, considerando apenas suas implicações a nível clássico utilizando a aproximação slow-roll. Finalmente, analisaremos o potencial taquiônico como sendo o potencial do in?aton e exploramos suas consequências. Como suporte, há quatro apêndices contendo alguns aspectos de Teoria de Cordas, Relatividade Geral, Cosmologia e alguns cálculos relevantes que foram omitidos ao longo da tese
Keywords: Modelos de corda; Cosmologia